Developing participatory tourism in Milan, Italy - Chiara Rabbiosi (Via@)
This article explores the social and spatial implications of new itineraries, sites and services whose success rests on opportunities for residents and tourists to meet, and possibly hybridize. This encounter is considered in reference to the changing relationship between cities, culture and tourism. Two initiatives based in Milan serve as comparative case studies. Piacere, Milano (Milano, nice to meet you) was launched in 2015, while the city was hosting the Universal Exhibition position, and consists of coordinating Milanese residents willing to invite a tourist for dinner or to take them on a walk for free. MygranTour is part of a European network supporting intercultural dialogue by involving migrants in the development of tourist itineraries. This programme has been active in Milan since 2011. Both these initiatives contribute to fostering new sets of images of Milan, and to legitimising new urban geographies from the bottom up. They also stimulate a reversal of the traditional hierarchy between tourists and residents. Major critical aspects are expressed in reference to different levels of analysis, such as in relation to the capacity building scope of initiatives, or how they might reproduce cultural stereotypes. The paper concludes by calling for more extensive integration of tourism into urban policies, by considering implications of tourism beyond the economic.